BIODIVERSITY OF GROUND SURFACE INSECTS IN SWEET ORANGES IN MOUNT RINJANI NATIONAL PARK - Andini, Baiq Yuni; Sazali, Munawir (Jurnal Biosains Pascasarjana, 2025)
This study aims to identify the diversity of surface-dwelling insects in Jeruk Manis, located within Gunung Rinjani National Park, and to analyze species diversity, dominance, and evenness indices. A survey method employing stratified random sampling based on habitat type was applied. Insect sampling was conducted at eight observation points on April 26, 2025. The study identified seven species of surface-dwelling insects: Largidae, Pachycondyla, Tapinoma sessile, Calliptamus italicus, Gray bird grasshopper, Pyrrhocoridae, and Thanasimus formicarius. Data analysis using the Shannon-Wiener Diversity Index yielded a diversity value (H') of 2.70, indicating a moderate level of species diversity. The Dominance Index (C) of 0.126 suggests that no single species dominates the community. However, the Evenness Index (J'), which varies between 0.126 and 7.397, reveals an uneven distribution of individuals among species, with certain species exhibiting significantly higher abundance than others. This research contributes to a deeper understanding of the insect ecosystem in the region and highlights the crucial role of surface-dwelling insects as bioindicators of environmental health.